الشيخ عليّ بن خضر العَمْرُوسِيّ ومنهجه في شرحِهِ عَلَى مُخْتَصَرِ خَلِيل (ت: 1173 هـ) - القلاي عبدالرحمن بدر (Al-Qurtas, 2026)
الشيخ عليّ بن خضر العَمْرُوسِيّ ومنهجه في شرحِهِ عَلَى مُخْتَصَرِ خَلِيل (ت: 1173 هـ)